Pleadings, minutes of public sittings and documents. Mémoires, procès-verbaux des audiences publiques et documents (Pleadings, minutes of public sittings, and documents ;, 2015)
The International Tribunal for the Law of the Sea is an international court with competence to settle disputes concerning the law of the sea. It is a central forum for the settlement of disputes relating to the interpretation and application of the United Nations Convention on the Law of the Sea. This volume contains the texts of written pleadings, minutes of public sittings and other documents from the proceedings in The "Arctic Sunrise" Case (Kingdom of the Netherlands volume Russian Federation), Provisional Measures . The documents are reproduced in their original language. The Tribunal delivered its Order on 22 November 2013. It is published in Reports of Judgments, Advisory Opinions and Orders 2013 (ITLOS Reports 2013) . The written pleadings, minutes of public sittings and other documents from the proceedings in The M/V "Louisa" Case (Saint Vincent and the Grenadines volume Kingdom of Spain) , Provisional Measures, have been published in the volume ITLOS Pleadings, Minutes and Documents 2009-2010 , Vol. 15, Part II. Le Tribunal international du droit de la mer est une juridiction internationale qui a compétence en matière de règlement des différends relatifs au droit de la mer. Il est une instance centrale pour le règlement des différends relatifs à l'interprétation et à l'application de la Convention des Nations Unies sur le droit de la mer. Le présent volume contient le texte des pièces de la procédure écrite, des procès-verbaux des audiences publiques et d'autres documents relatifs à la procédure dans l'Affaire de l'« Arctic Sunrise » (Royaume des Pays-Bas c. Fédération de Russie), mesures conservatoires . Les documents sont reproduits dans la langue originale utilisée. Le Tribunal a rendu son ordonnance le 22 novembre 2013. L'ordonnance est publié dans Recueil des arrêts, avis consultatifs et ordonnances 2013 (TIDM Recueil 2013) . Les pièces de la procédure écrite, des procès-verbaux des audiences publiques et d'autres documents produits dans l'Affaire du navire « Louisa » (Saint-Vincent-et-les Grenadines c. Royaume d'Espagne) , mesures conservatoires, sont publiés dans le volume : TIDM Mémoires, procès-verbaux et documents 2009-2010 , volume 15, partie II.